Tracing Back Clinical Campylobacter jejuni in the Northwest of Italy and Assessing Their Potential Source - Di Giannatale, Elisabetta; Garofolo, Giuliano; Alessiani, Alessandra; Di Donato, Guido; Candeloro, Luca; Vencia, Walter; Decastelli, Lucia; Marotta, Francesca (Frontiers in Microbiology, 2016)
Foodborne campylobacteriosis is caused mainly by the handling or consumption of undercooked chicken meat or by the ingestion of contaminated raw milk. Knowledge about the contributions of different food sources to gastrointestinal disease is foundamental to prioritize food safety interventions and to realize adequate control strategies. Assessing the genetic diversity among Campylobacter species is essential to our understanding of their epidemiology and population structure. We molecularly characterized 56 Campylobacter jejuni isolates (31 from patients hospitalized with gastroenteritis, 17 from raw milk samples and 8 from chicken samples) using multilocus sequence typing (MLST) and pulsed field gel electrophoresis (PFGE) in order to trace the source of the disease. We also used a population genetic approach to investigate the source of the human cases from six different reservoirs of infection. MLST identified 25 different sequence types and 11 clonal complexes (CCs; 21, 658, 206, 353, 443, 48, 61, 257, 1332, 354, 574) and these included several alleles not cited previously in the PubMLST international database. The most prevalent CCs were 21, 206 and 354. PFGE showed 34 pulsotypes divided between 28 different clusters. At the fine scale, by means of PFGE and MLST, only two human cases were linked to raw milk, while one case was linked to chicken meat. The investigation revealed the presence of several genotypes among the human isolates, which probably suggests multiple foci for the infections. Finally the source attribution model we used revealed that most cases were attributed to chicken (69.75%) as the main reservoir in Italy, followed to a lesser extent by the following sources: cattle 8.25%; environment 6.28%; wild bird 7.37%; small ruminant 5.35% and pork 2.98%. This study confirms the importance of correlating epidemiological investigations with molecular epidemiological data to better understand the dynamics of infection.